Facial height proportion based on Angle’s malocclusion in Deutero-Malayids - Aulia Rohadatul Aisy; Avi Laviana; Gita Gayatri (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: Facial aesthetics are closely related to the harmonious proportions of the facial components. One of the components is facial height. The reference of facial height proportion of certain racial groups needs to be known by orthodontists and surgeons to create treatment outcomes that can be specifically designed for these particular demographics. One of the factors that can affect facial height proportion is malocclusion. Purpose: This study aimed to determine facial height proportion based on Angle’s classification of malocclusion in Deutero-Malayids. Methods: This study used a descriptive cross-sectional method, which was conducted on 116 Deutero-Malayid subjects. The subjects’ malocclusion was first examined using Angle’s classification of malocclusion. Upper and lower facial height were then measured to determine the proportion of these dimensions. The results were then grouped based on each malocclusion class. Results: It was found that the upper and lower facial height proportions in the class I malocclusion group were 46.74% and 53.26% in males and 47.52% and 52.48% in females, respectively. The upper and lower facial height proportions in the class II malocclusion group were 48.46% and 51.54% in females. Upper and lower facial height proportions in the class III malocclusion group were 45.31% and 54.69% in males and 46.29% and 53.71% in females, respectively. Conclusion: The largest proportion of upper facial height in Deutero-Malayids was seen in the class II malocclusion group, followed by class I and class III. The largest proportion of lower facial height in Deutero-Malayids was seen in the class III malocclusion group, followed by class I and class II.